ANALISIS PROSES PIROLISIS LIMBAH PLASTIK HDPE DAN PET: PENGARUH TEMPERATUR DAN WAKTU REAKSI DALAM UPAYA DAUR ULANG PLASTIK - A yan Sabitah; Ichwan Noor Ardiyat; Misbachudin Misbachudin; Ikna Urwatul Wusko; Rahma Pitria Ningsih (Scientific Journal of Mechanical Engineering Kinematika, 2024)
Plastic waste is a significant environmental challenge, but its management is still not fully effective. Common methods such as garbage disposal, combustion, and recycling have their limitations, especially the release of harmful compounds during low-temperature plastic burning. Therefore, research continues to look for better solutions. One promising approach is pyrolysis, a process in which plastic molecules break down at high temperatures in an inert gas environment. Pyrolysis produces solid, liquid, and gas products, with liquids potentially functioning as biofuels after further repairs. The study discussed the influence of temperature and time on the pyrolysis of HDPE and PET plastics. The results showed that temperature is a critical factor, with a limited reaction temperature between 500 Â°C and 700 Â°C. Results of the pyrolyse process include tar/liquid and char/ solid residues. Strangely, 3 kg HDPE produce the highest amount of tar, about 973 ml, while 3 kg PET produce the least, about 89 ml. Overall, achieving a uniform heat distribution and optimal temperature is crucial to improving the efficiency and quality of the pirolysis product.